The Impact of Preoperative Fasting Duration on Blood Glucose and Hemodynamics in Children - Pouran Hajian; Minoo Shabani; Elham Khanlarzadeh; Mahshid Nikooseresht (Journal of Diabetes Research)
Background. Prolonged preoperative fasting is one of the concerns of pediatricians and anesthesiologists in pediatric surgery. The aim of this study was to assess the impact of preoperative fasting duration on blood glucose and hemodynamics in children. Methods. This cross-sectional study was conducted on 50 children who were between the ages of 3 and 12 years in Besat Hospital, Hamedan, Iran. The time of the last solid and liquid meal taken by child were recorded based on interview with the parents. The first blood glucose test was obtained in the operation room, and the second test was performed 20 minutes after induction of anesthesia by glucometer. Systolic blood pressure (SBP), mean arterial pressure (MAP), and heart rate (HR) were recorded before anesthesia induction and in five-minute intervals in the first 20 minutes of surgery. Results. The mean age of the children was 6.63 (SD 1.85) years. Mean blood glucose 20 minutes after surgery was 101.17 (SD 92) mg/dl, which was significantly higher than the baseline values (87.66 (SD 11.84) mg/dl) (P<0.001). The comparison of mean blood glucose level between groups of fasting with different duration for solids (<12 hours and >12 hours) and for liquids (<6 hours and >6 hours) revealed no significant difference in either groups (P>0.05). No significant correlation was observed between blood glucose level at the induction of anesthesia with weight and age (P>0.05). There was a significantly negative correlation between duration of fasting for liquids and SBP (P>0.05). Conclusion. Prolonged preoperative fasting cannot affect blood glucose in children; however, maybe it has impact on systolic blood pressure.